Echocardiographic assessment of insulin‐like growth factor binding protein‐7 and early identification of acute heart failure. (14th May 2020) - Kalayci, Arzu; Peacock, W. Frank; Nagurney, John T.; Hollander, Judd E.; Levy, Phillip D.; Singer, Adam J.; Shapiro, Nathan I.; Cheng, Richard K.; Cannon, Chad M.; Blomkalns, Andra L.; Walters, Elizabeth L.; Christenson, Robert H.; et al.
Abstract: Aims: Concentrations of insulin‐like growth factor binding protein‐7 (IGFBP7) have been linked to abnormal cardiac structure and function in patients with chronic heart failure (HF), but cardiovascular correlates of the biomarker in patients with more acute presentations are lacking. We aimed to determine the relationship between IGFBP7 concentrations and cardiac structure and to evaluate the impact of IGFBP7 on the diagnosis of acute HF among patients with acute dyspnoea. Methods and results: In this pre‐specified subgroup analysis of the International Collaborative of N‐terminal pro‐B‐type Natriuretic Peptide Re‐evaluation of Acute Diagnostic Cut‐Offs in the Emergency Department (ICON‐RELOADED) study, we included 271 patients with and without acute HF. All patients presented to an emergency department with acute dyspnoea, had blood samples for IGFBP7 measurement, and detailed echocardiographic evaluation. Higher IGFBP7 concentrations were associated with numerous cardiac abnormalities, including increased left atrial volume index (LAVi; r = 0.49, P < 0.001), lower left ventricular ejection fraction ( r = −0.27, P < 0.001), lower right ventricular fractional area change ( r = −0.31, P < 0.001), and higher tissue Doppler E/e′ ratio ( r = 0.44, P < 0.001). In multivariable linear regression analyses, increased LAVi ( P = 0.01), lower estimated glomerular filtration rate ( P = 0.008), higher body mass index ( P = 0.001), diabetes ( P = 0.009), and higher concentrations of amino‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP, P = 0.02) were independently associated with higher IGFBP7 concentrations regardless of other variables. Furthermore, IGFBP7 (odds ratio = 12.08, 95% confidence interval 2.42–60.15, P = 0.02) was found to be independently associated with the diagnosis of acute HF in the multivariable logistic regression analysis. Conclusions: Among acute dyspnoeic patients with and without acute HF, increased IGFBP7 concentrations are associated with a range of cardiac structure and function abnormalities. Independent association with increased LAVi suggests elevated left ventricular filling pressure is an important trigger for IGFBP7 expression and release. IGFBP7 may enhance the diagnosis of acute HF.